Italijanske operne predstave pri Auerspergih sredi 17. stoletja - drobtinica k slovenskemu glasbenemu zgodovinopisju - Kokole, Metoda (Muzikološki zbornik, 1999)
The article brings chronologically organised history of research into this subject, beginning with the short remarks by the historians in the second half of the 19th century, contributions by music and theatre historians up to the World War II, and new discoveries and conclusions of Slovenian musicologists after 1958. In the present state of our knowledge it is possible to conclude that the operas La gara, Le vicende del tempo and L'Argia of 1652 and 1655 were not performed in Ljubljana. As for the performance of the Italian opera in 1660 it seems pousible to assume that it was an opera following examples of contemporary Venetian models.
Keywords: 17.st.; Auersperg (rodbina); glasba; italijanska opera; music; operne predstave; zgodovinski pregledi